Concurrent repeated-sprint and resistance training with superimposed vibrations in rugby players - Suarez-Arrones, L.; Tous-Fajardo, J.; Nunez, J.; Gonzalo-Skok, O.; Gálvez, J.; Mendez-Villanueva, A. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To examine the effect of repeated-sprint training (RST) vs combined RST and resistance training with superimposed vibrations on repeated-sprint ability (RSA) and lower-body power output in male rugby players. Methods: Players were divided into 2 training groups. One group performed RST (n = 10) 2 d/wk and the other performed RST 1 d/wk and squat resistance training with superimposed vibrations on the second day (RS+ST; n = 10). The squat training was carried out with a volume similar (ie, number of sets and repetitions) to that of the RST. The training period lasted 6 wk, and it was carried out as a supplement to the regular rugby training sessions. Results: Substantial improvements in RSA mean time (RSAmean; +2.3%/ES: 0.77 vs +4.1%/ES: 0.91), RSA percent decrement (%Dec; -25.6%/ES: 1.70 vs -23.2%/ES: 0.99), and squat absolute power output (+5.0%/ES:0.36 vs +17.2%/ES: 0.93) were obtained in RST and RS+ST, respectively. Substantial improvements in RSA best time (RSAbest; +2.6%/ES: 0.61) and squat power output normalized to body mass (+18.6%/ES: 0.76) only occurred in RS+ST. Both pretest and posttest RSAmean were largely correlated with the RSAbest. However, there were only unclear, small to moderate correlations between individual changes in squat power output and either RSAmean or RSAbest. Conclusion: Combined RST and resistance training induced improvements of greater magnitude in both repeated-sprint performance and muscle power output than the RST alone. The lack of substantial correlations between individual changes in repeated-sprint and muscle-power performance suggests that the same subjects were not systematically low or high responders to both RST and strength training.